Determinants of tuberculosis in countries of Latin America and the Caribbean - Gustavo Bergonzoli; Luis G. Castellanos; Rodolfo Rodríguez; Lina María Garcia
ABSTRACT Objectives To explore the relationships among social, economic, environmental, and health services determinants of tuberculosis (TB) morbidity and mortality, and to identify the mechanisms that mediate such associations in countries of Latin America and the Caribbean (LAC). Methods This was an ecological study of 26 LAC countries that had accurate data available on 38 selected variables for the year 2010. The countries represented 99% of the TB burden in LAC. Multivariate linear regression was used to identify associations among determinants of health and TB morbidity and mortality. Results TB-HIV coinfection and multidrug resistant TB (MDR-TB) in previously treated cases were found to be positively associated to TB morbidity and negatively associated to improved basic sanitation and water coverage-pointing to an increase of TB morbidity in the first two variables and a decrease of TB morbidity in the last two. Regarding TB mortality, indigenous people and MDR-TB in previously treated cases were positively associated. In contrast, literacy among women, basic sanitation, water coverage, and nutritional status were negatively associated to mortality, denoting that improvements in these areas could reduce TB mortality. Conclusions The study findings support intersectoral actions that address social, economic, environmental, and health services determinants within the Stop TB strategy. The mechanisms by which social determinants of health affect current trend outcomes extend beyond medical interventions to control TB, but more research is needed to understand how and to develop actionable recommendations.